Specific adaptation of Ustilaginoidea virens in occupying host florets revealed by comparative and functional genomics - Zhang, Yong; Zhang, Kang; Fang, Anfei; Han, Yanqing; Yang, Jun; Xue, Minfeng; Bao, Jiandong; Hu, Dongwei; Zhou, Bo; Sun, Xianyun; Li, Shaojie; Wen, Ming; et al. (Springer, 2014)
Ustilaginoidea virens (Cooke) Takah is an ascomycetous fungus that causes rice false smut, a devastating emerging disease worldwide. Here we report a 39.4 Mb draft genome sequence of U. virens that encodes 8,426 predicted genes. The genome has ~25% repetitive sequences that have been affected by repeat-induced point mutations. Evolutionarily, U. virens is close to the entomopathogenic Metarhizium spp., suggesting potential host jumping across kingdoms. U. virens possesses reduced gene inventories for polysaccharide degradation, nutrient uptake and secondary metabolism, which may result from adaptations to the specific floret infection and biotrophic lifestyles. Consistent with their potential roles in pathogenicity, genes for secreted proteins and secondary metabolism and the pathogen–host interaction database genes are highly enriched in the transcriptome during early infection. We further show that 18 candidate effectors can suppress plant hypersensitive responses. Together, our analyses offer new insights into molecular mechanisms of evolution, biotrophy and pathogenesis of U. virens.